Bio-divergent identity therapy: Habilitating identity from the biographical disruption of diagnosis in sci-fi fantasy culture - Meir Y. Barth (Elsevier, 2022)
This article seeks to address a gap in the therapeutic arsenal for those diagnosed with chronic conditions. Where such diagnoses disrupt patients' identities, a form of identity habilitation is needed. By building on pre-existing models for therapy related to identity in conjunction with a multi-method investigation of in situ practices enacted by the bio-divergent (disability) community at a sci-fi fantasy convention as a manifestation of sci-fi fantasy culture more broadly, this article aims to establish the utility of formulating an empirically-based model for a form of identity habilitation practices for redressing the impacts of diagnoses.